Henry Notaker: Den norske men yen - Davidson, Alan E (Petits Propos Culinaires, 1993)
Henry Notaker: Den norske men yen: Oslo, Det Norske Samlaget, 1991 : 192 pp, numerous colour illustrations of old Norwegian menus, afterword, two-page English summary, limp cloth binding, price not stated.